The causes and impacts of scope creep in construction contracts for Mpumalanga Province - Mnguni, Nomthandazo (My University, 2021)
Purpose: Without a doubt, scope creep significantly affects project budget and objectives. This research evaluates the various causes and impacts resulting from scope creep in construction contracts in Mpumalanga Province, South Africa. Methodology: Data gathering was done by means of a structured online questionnaire survey which targeted 55 professionals working in the construction industry. The research used the non-probability sampling technique due to difficulties in getting the total number of construction professionals working in the province. The research adopted purposive sampling leading to an 80% response rate. Descriptive statistics was employed in analysing the survey response data. Findings: Poor scope definition had the highest Mean Score (MS)of 4.341 (in the range of agree) and was ranked topmost amongst the 6 causes of scope creep constructs. By and large, the lowest-ranked item was project lifecycle, with a MS of 3.386 (in the range of undecided). The top three ranked impacts of scope creep were, poor scope definition with a MS of 4.341 (in the range of above average), underestimating complexity with a MS of 4.182 (in the range of above average), and poor communication with a MS of 4.023 (in the range of above average).Research limitations/implications: The general outcome from the research is that from the initiation stage, project scope is not sufficiently presented and thus, clients and advisors should clearly define project needs upfront to avoid scope creep. Furthermore, it is evident that, extra awareness of the causes and impacts of scope creep coupled with the introduction and effective implementation of scope management system(s) improves efficiency within the construction industry. Moreover, project stakeholders should strive to enhance their understanding of project management as this will help to reduce or eliminate scope creep. The resultant effect will be improvements in project delivery within the construction industry. Originality/ Value: The originality of the research is based on specifically investigating the causes and impacts of scope creep in construction contracts in Mpumalanga Province
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in the field of Construction Management